Historical economic growth and innovation on the ground of modern Belarus - Kovalev, Mikhail M. (Journal of the Belarusian State University. Economics, 2019)
Forecasting the past of Belarusian lands from the standpoint of modern concepts as «GDP» and «innovation» is considered. The reasons for the growing over the centuries of the lagging of well-being (per capita GDP at PPP) of Belarusians from Western Europeans are revealed. The factors that influenced the reduction of this gap after independence are enumerated.